Rat hippocampal alterations could underlie behavioral abnormalities induced by exposure to moderate noise levels - Urán, Soledad Lucía (2012)
Noise exposure is known to affect auditory structures in living organisms. However, it should not be ignored that many of the effects of noise are extra-auditory. Previous findings of our laboratory demonstrated that noise was able to induce behavioral alterations that are mainly related to the cerebellum (CE) and the hippocampus (HC). Therefore, the aim of this work was to reveal new data about the vulnerability of developing rat HC to moderate noise levels through the assessment of potential histological changes and hippocampal-related behavioral alterations. Male Wistar rats were exposed to noise (95-97 dB SPL, 2 h daily) either for 1 day (acute noise exposure, ANE) or between postnatal days 15 and 30 (sub-acute noise exposure, SANE). Hippocampal histological evaluation as well as short (ST) and long term (LT) habituation and recognition memory assessments were performed. Results showed a mild disruption in the different hippocampal regions after ANE and SANE schemes, along with significant behavioral abnormalities. These data suggest that exposure of developing rats to noise levels of moderate intensity is able to trigger changes in the HC, an extra-auditory structure of the Central Nervous System (CNS), that could underlie the observed behavioral effects.